Podejście do motywowania w warunkach postępujących zmian - Kopertyńska, Maria Wanda (Approach to motivation in varying conditions, 2005)
The article presents the approach to employee’s motivation in terms of changes in the economic conditions. These changes are the results of globalization processes, development of information and telecommunication systems as well as increased significance of applied managerial knowledge
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 201-210